Mapas de Radiación ultravioleta en Costa Rica - Wright, Jaime (2009)
Ultraviolet radiation (UV) contributes relatively little to the solar spectrum. However it is very important because it is biological very active. The aim of this work is to evaluate the levels of ultraviolet solar radiation (UV) using solar radiation maps designed for the territory of Costa Rica created with the software Surfer 8. The data of UV radiation – utilized in the creation of the maps – were predicted in eighty-three geographical locations by an atmospheric spectral model, which is physically established, this model utilizes as necessary input data: the date and hour, identifying place by the latitude, length and height of the land above sea level, the value of the vertical column of the ozone, the superficial albedo and the atmospheric turbidity parameters. The estimation differs in a 3% with the experimentation data made in situ. The model estimate ultraviolet radiation under clear skies conditions; this is the maximum possible energy which is obtained in each locality. This is important at the moment to evaluate the harmful effects for the human health can cause the maximum intensity in this important band of the solar spectrum. Among the most noticeable results can be mentioned an increase of 23%  with the altitudes, among the lower places (sea level) and higher places (hills and mountains). It was also found an increment greater that 27% between the months of fewer solar radiation (December) and greater solar radiation (Apri). This theme is of special interest due to the growing number of people that displace during different times of the year to altitudes greater than 2000 m in activities relating to the tourism, recreation and work. In this case these people receive important increments in the levels of ultraviolet solar radiation in clear sky conditions.